El impacto del Bono Juancito Pinto: Un análisis a partir de micro simulaciones - Ernesto Yá\~nez Aguilar (Universidad Católica Boliviana, Instituto de Investigaciones Socio-Económicas (IISEC), 2012)
– This paper presents an appraisal Juancito Pinto from the use of micro simulation techniques. Specifically, it assesses the impact on school attendance, poverty and inequality in income distribution. The results suggest that the BJP has had a positive impact on reducing truancy in primary schools, has helped reduce poverty levels in addition to improved income distribution, especially in rural areas of the country -. Possible improvements to the BJP would be linked to differentiate the amount transferred in terms of area of residence which would bring additional benefits without significantly altering the program's administrative costs.
Keywords: I38; O12; 330; Ex-ante; micro simulation; conditional transfers; education; Juancito Pinto; Bolivia